2003
DOI: 10.1051/forest:2003066
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil surface disturbances after logging on plant functional types

Abstract: -Soil surface disturbances after logging influence plant species diversity. To estimate these effects, the objective of the present study was to test three hypotheses: (1) each soil surface disturbance type is characterized by a group of plant species that emerges following the disturbance, (2) each emergent group of plant species has distinct, recognizable biological traits, (3) in two different bio-geographic plant communities, each soil surface disturbance type is characterized by the same set of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Moreover, plant functional traits may be more important than abiotic factors to determine the species dynamics of the herbaceous community. A similar finding was obtained by Gondard and Deconchat [24].…”
Section: Species Richness and Species Profilesupporting
confidence: 77%
See 2 more Smart Citations
“…Moreover, plant functional traits may be more important than abiotic factors to determine the species dynamics of the herbaceous community. A similar finding was obtained by Gondard and Deconchat [24].…”
Section: Species Richness and Species Profilesupporting
confidence: 77%
“…The functional traits may also be helpful to understand and predict the distribution and abundance of plant species in forest habitat [26,65]. Moreover some authors demonstrated a relation between functional traits and disturbance or management practices and assumed that there is a pattern of response according to the species traits [15,24,34]. Therefore the functional and compositional parts of the diversity are crucial for conservation purposes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In managed forests, harvesting as well as soil disturbance and compaction due to heavy machinery increase species diversity [8,9,12,30,55]. Schall [53], Glowienka [29] and Mrotzek et al [45] compared the vegetation along forest roads with the adjacent stands.…”
Section: Discussionmentioning
confidence: 99%
“…Most German forests are subdivided by dense forest road and track systems [5,17,25], of which the consequences are harvesting damage to stand and soil as well as area loss for timber production [3,17,62]. However, ecological aspects of skidding tracks on herb layer vegetation have hardly been considered [11,12,30]. Also net nitrogen mineralization which is an important factor in ecosystem functions [19] might be influenced along skidding tracks.…”
Section: Introductionmentioning
confidence: 99%